2019
DOI: 10.1186/s13287-018-1107-7
|View full text |Cite
|
Sign up to set email alerts
|

BMP-dependent, injury-induced stem cell niche as a mechanism of heterotopic ossification

Abstract: BackgroundHeterotopic ossification (HO), either acquired (aHO) or hereditary, such as fibrodysplasia ossificans progressiva (FOP), is a serious condition without effective treatment. Understanding of the core process of injury-induced HO is still severely limited.MethodsDouble-pulse thymidine analog labeling was used to explore the distinctive domains evolved in injury-induced lesions in an animal model of HO (Nse-BMP4). Histological studies were performed to see whether a similar zonal pattern is also consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 38 publications
0
39
1
Order By: Relevance
“…A recent study showed that Gli1labeled adult mesenchymal stem/progenitor cells contributed to endochondral heterotopic ossification (7). Ablation of Hh signaling can inhibit the HO process in an Mkx-deficient mouse model and trauma-induced HO mouse model (35,36). Activating Hh signaling is…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that Gli1labeled adult mesenchymal stem/progenitor cells contributed to endochondral heterotopic ossification (7). Ablation of Hh signaling can inhibit the HO process in an Mkx-deficient mouse model and trauma-induced HO mouse model (35,36). Activating Hh signaling is…”
Section: Discussionmentioning
confidence: 99%
“…Although it is always difficult to extrapolate from animal models of disease to humans, the cellular and molecular features of human HO are very similar to what is observed in Nse-BMP4 mice. 28 Thus we hypothesize that a BMP-dependent, injury-induced stem cell niche is a common mechanism of HO 28 and that the altered immune homeostasis observed in the animal model are part of the process in humans. Importantly, we specifically used FDA-approved IC inhibitors in these studies to enhance the potential translational implications.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recently, it was shown that local dysregulation of Hh signaling participates in the pathophysiology of murine muscle injury model of HO. 14,15 Furthermore, these lineage tracing studies suggested an involvement of Hh target transcription factor, Gli1, in endochondral bone formation. 14,15 Currently, there is no effective and safe HO prophylaxis treatment.…”
Section: Introductionmentioning
confidence: 90%
“…14,15 Furthermore, these lineage tracing studies suggested an involvement of Hh target transcription factor, Gli1, in endochondral bone formation. 14,15 Currently, there is no effective and safe HO prophylaxis treatment. Radiation therapy and indomethacin are the most widely used therapeutic approaches in the setting of post-surgical heterotopic ossification prophylaxis, with evidently many hazards and shortcomings.…”
Section: Introductionmentioning
confidence: 90%